RESONANT IR ABSORPTION IN NANOTHIN MOLECULAR FILMS - S. Pelemiš; S. Armaković; J. P. Šetrajčić (Journal of Engineering & Processing Management, 2010)
This paper presents results of theoretical research in changed optical properties due to the presence of boundaries and changes of boundary parameters in nanofilm-molecular crystals. The energy spectrum of excitons and their spatial distribution along the axis limits (in layers) were found through analytical and numerical calculations. The relative permittivity of these ultrathin dielectric films was determined and the influence of boundary parameters on occurrence of discrete (by frequencies) and selective (per layers) absorption was analyzed. We found conditions for the appearance of the smallest number of resonant absorption peaks (absorption lines) in the border surfaces of the observed film structure.
Keywords: excitons; absorption; film